Depopulation in the Visok micro-region: Toward demographic and economic revitalization - Marković Ksenija; Radivojević Aleksandar R.; Marković Rastko S. (Open Geosciences, 2025)
The demographic potential of the settlements in the Visok micro-region has been significantly disrupted since 1948. The latest census (2022) shows that the Visok micro-region now consists of very small settlements, all with fewer than 100 inhabitants. In all 22 villages of the Visok micro-region, there are only 504 inhabitants, with unfavorable age structures. The region’s average age has remained above 65 for the last 30 years, significantly older than the surrounding areas. Low salaries, bad infrastructure, and the industrialization of Pirot City represent the main reasons for depopulation. The Zavoj Lake catastrophe caused three villages to be submerged, which accelerated depopulation even more. Most of the remaining inhabitants are engaged in farming or work in the construction, stone, and forestry industries, with sheep farming being a notable tradition. The local population shows strong ecological awareness, advocating for industries that align with nature, creating an ideal environment for nature enthusiasts and scientists. The only way for revitalization is to have organized seasonal migrations based on the summer tourist season. The main aim for revitalization would be a national-level plan for creating a brand of untouched nature, with traditional agricultural products for the complete experience.